Management of Pring Sewu Cultural Market Using a Community-Based Management (CBM) Approach: Pengelolaan Pasar Budaya Pring Sewu Dengan Pendekatan Community Based Management (CBM) - Naila Syafa Rahmaniyah; Lailul Mursyidah (Jurnal Pemerintahan dan Politik, 2026)
Purpose: This study aims to analyze the management of the community-based pring sewu cultural market through a Community Based Management (CBM) approach in Binangun Hamlet as part of the development of a tourist village in Plintahan Village, Pandaan District, Pasuruan Regency. Design: This study uses a qualitative approach through interviews, observations, and documentation to understand the management of the community-based pring sewu cultural market. Findings: The results of the study show that the management of the pring sewu cultural market is carried out in a participatory manner by the Binangun Hamlet Community through mutual agreement, the application of local norms, and flexible division of roles. The initiative to use bamboo coins as a transaction tool is a form of local ownership and innovation that supports the economic sustainability of MSME actors while strengthening the identity of culture-based tourism villages. Practical Implication: The findings of this study show that community-based market management can be a model for strengthening tourism villages that rely on the participation and independence of local communities. Originality: This research provides an empirical contribution to the application of Community Based Management (CBM) theory through community participation, local ownership and initiatives, local rules and norms, division of roles and responsibilities, and economic sustainability in the management of cultural markets as part of the development of community-based tourism villages.